Pelapisan Lilin Karnauba dan Kitosan untuk Mempertahankan Mutu Wortel Kupas - Trisma Rezeki Zairisman; I Wayan Budiastra; Sugiyono Sugiyono (PERTETA, 2017)
AbstractCarrot is one kind of vegetables that is highly consumed in Indonesia and foreign countries. Carrots are usually marketed in the form of unpeeled carrots, but now the demand of peeled carrots or minimally processed carrots increases significantly, especially for export. Unfortunately, the peeled carrot usually is more perishable than unpeeled carrots. Therefore, postharvest technology to maintain the quality of peeled carrot is required, one of them is wax coating technology. The aim of this research was to determine the best treatment of coating and storage temperature to maintain quality of peeled carrot during cold storage. Three kinds of storage temperatures (5, 10, 15 °C) and three kinds of coating (carnauba wax, chitosan, carnauba wax+chitosan) were applied in this research. The change of quality of peeled carrot during storage such as moisture content, weight loss, respiration rate, total plate count, color and organoleptic test was investigated. The results showed that the storage temperature significantly influenced the quality parameters analyzed. Coating did not significant affect the quality parameters of peeled carrot. The temperature of 5 °C suppress damage of peeled carrots during storage compared to other temperatures. Chitosan coating combined with storage temperature of 5 °C is the best postharverst treatment for pelled carrot, with the shelf-life of 9 days. AbstrakWortel merupakan salah satu sayuran yang cukup banyak dikonsumsi oleh konsumen dalam dan luar negeri. Biasanya wortel dipasarkan dalam bentuk wortel tanpa kupas, namun saat ini permintaan wortel kupas atau wortel terolah minimal semakin besar khususnya dari Singapura. Wortel dalam keadaan terolah minimal lebih cepat busuk dibandingkan dengan wortel tanpa kupas, sehingga diperlukan teknologi pascapanen untuk mempertahankan mutu dari wortel kupas, salah satunya dengan pelapisan lilin. Penelitian ini bertujuan untuk menentukan jenis pelilinan dan suhu penyimpanan dingin terbaik untuk mempertahankan mutu wortel kupas. Penelitian ini menggunakan 3 jenis suhu (5, 10, 15oC) dan 3 jenis pelapisan (lilin karnauba, kitosan dan kombinasi). Parameter mutu yang dianalisis adalah kadar air, susut bobot, laju respirasi, total mikroba, warna dan uji organoleptik. Hasil penelitian menunjukkan bahwa suhu penyimpanan berpengaruh signifikan terhadap parameter mutu yang dianalisis. Pelapisan tidak berpengaruh signifikan terhadap parameter mutu wortel kupas. Suhu 5oC dapat menghambat kerusakan wortel kupas selama penyimpanan dibandingkan dengan suhu lainnya. Pelapisan dengan kitosan dan suhu penyimpanan 5oC adalah perlakuan terbaik untuk wortel kupas dengan umur simpan 9 hari.